Expression of Dectin-1 and Enhanced Activation of NALP3 Inflammasome Are Associated with Resistance to Paracoccidioidomycosis - Vera Lucia Garcia Calich; Claudia eFeriotti; Silvia B. Bazan; Flavio Vieira Loures; Eliseu Frank Araujo; Tania A. Costa (Frontiers in Microbiology, 2015)
Dectin-1 is a pattern recognition receptor (PRR) that recognizes β-glucans and plays a major role in the immunity against fungal pathogens. Paracoccidioides brasiliensis, the causative agent of paracoccidioidomycosis, has a sugar-rich cell wall mainly composed of mannans and glucans. To investigate the role of dectin-1 in the innate immunity of resistant (A/J) and susceptible (B10.A) mice to P. brasiliensis infection, we evaluated the role of curdlan (a dectin-1 agonist) and laminarin (a dectin-1 antagonist) in the activation of macrophages from both mouse strains. We verified that curdlan has a negligible role in the activation of B10.A macrophages but enhances the phagocytic and fungicidal abilities of A/J macrophages. Curdlan up-regulated the expression of costimulatory molecules and PRRs in A/J macrophages that express elevated levels of dectin-1, but not in B10.A cells. In addition, curdlan treatment inhibited arginase-1 and enhanced NO-synthase mRNA expression in infected A/J macrophages but had not effect in B10.A cells. In contrast, laminarin reinforced the respective M2/M1 profiles of infected A/J and B10.A macrophages. Following curdlan treatment, A/J macrophages showed significantly higher Syk kinase phosphorylation and expression of intracellular pro-IL-1β . These findings led us to investigate if the NRLP3 inflammasome was differently activated in A/J and B10.A cells. Indeed, compared with B10.A cells A/J macrophages showed an increased expression of NALP3, ASC and IL-1β mRNA. They also showed elevated caspase-1 activity and secreted high levels of mature IL-β and IL-18 after curdlan treatment and P. brasiliensis infection. Our data demonstrate that soluble and particulate β-glucans exert opposed modulatory activities on macrophages of diverse genetic patterns. Moreover, the synergistic action of dectin-1 and NALP3 inflammasome were for the first time associated with the innate response of resistant hosts to P. brasiliensis infection.